Peran Akuntansi Akad Musyarakah Dalam Meningkatkan Keberhasilan Pembiayaan Usaha Mikro: Studi Kasus Pada BPRS di Palembang - M. Daffa’ Nur Hidayat; Anugrah Danial Erlangga; Peny Cahaya Azwari (Kajian Ekonomi dan Akuntansi Terapan, 2025)
This study aims to explore the extent to which the application of accounting in the musyarakah contract affects the success of micro-business financing. The research was conducted at one of the Islamic Rural Financing Banks (BPRS) in Palembang. A qualitative approach was used to gain a deep understanding of the role of accounting in the implementation of the musyarakah contract, with a focus on the processes of recording, reporting, and financial supervision of micro-financing. The results indicate that the proper application of accounting in the musyarakah contract significantly contributes to the success of the financing. This is reflected in increased transparency, accountability, and the ability of micro-businesses to manage finances more effectively. The study recommends that BPRS intensify accounting support and education for customers to maximize the benefits of musyarakah financing.